UJI TOKSISITASEKSTRAK DAUN SIRSAK (Annona muricata L.) YANG BERPOTENSI SEBAGAI ANTIKANKER - Triyani Sumiati; Ferry Effendi; Rina arifah puspitasari (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2016)
Plant soursop (Annona muricata L.) is one of the Annonaceae familia. This plant has well-known in the society environment and it has been using as a traditional medicine. One of benefits of the soursop is can used as an algernative of cancer treatment. Until now not yet known scientifically whether soursop leaves have anticancer activity.This study aims to determine the potential toxicity of bioactive substances from the ethanol extract, of ethyl acetate and n-hexane of the soursop leaves as an anticancer agent by using Brine Shrimp Lethality Test (BSLT) method. This experimental As many as 100 larvas were use as research objects which divided into 3 groups. Each group consist of 10 larvas and the group repetition were done by randomly, three times per group. The extract concentration used in medium is 500, 100, 10 and as a control 0 ppm. Data obtained from counting the number of dead larvas (letal concentration 50 ppm) after 24 hours treatment. Based on the data obtained from LC50 of extract ethanol, ethyl acetate and n-hexane soursop leaves then determined by using probit analysis. The water content which contained in simplicia (drifed leaves) is 6,49%. The probit analysis results show that the ethanol extract have LC50 values of 86,45 ppm, 92,81 ppm of ethyl acetate extract and n-hexane extracts 37601,05 ppm. The distribution of ethanol and ethyl acetate extracts of soursop leaves in the experiments shown any potential toxicity against Artemia salina Leach, while the n-hexane extract of soursop leaves show no any potential toxicity to against Artemia salina Leach larvas.